Draft Annual Plan 1977-78 Government of Andhra Pradesh - Planning Commission (Planning Commission, 1977)
For the year 1976-77 Planning Commission approved Plan of Rs. 262.35 crores. Taking into account the minimum commitments in the various sectors of development and also the available resources, the plan outlay was subsequently increased to Rs. 281.50 crores.
Government of Andhra Pradesh, Finance and Planning (PLG Wing-IV) Department
Government of Andhra Pradesh, Finance and Planning (PLG Wing-IV) Department